Autoformação como exercício do tornar-se educador(a): uma reflexão sobre autoridade e microestética do cotidiano. - Nascimento, Isabel Cristina Cardoso de (2011)
How do educators experience their self-education in school and social projects when mediated by a day-by-day micro-aesthetics? Would there be an aesthetic sense in supporting our self-education? These questions outline the horizon at which this research aims: educational spaces outside the scope of official education. This paper proposes a way of self-configuration of the (self-) creation of an educator mediated by day-by-day micro-aesthetics. My methodology is based on the auto-biographical project (JOSSO), and thereby I discover stories of life in the dialogue between the educators who make up this path. For the analysis of educational places, I chose the group of women embroiderers, Projeto Social Criança Feliz; the pedagogical praxis of an art educator of the school Democrito Rocha and the work of a social educator, who involves the reconstitution of the Reisado in the community Ancurí. I make use of the Journal of Research as a way to authorize the construction of my observations and research in these photo-generated scenarios, such as pre-texts and texts that could provide visibility to the movement of aesthetic production of subjectivities and the people involved in research. To follow this proposition, I use the theoretical framework of Ostrower, Macedo, Warschauer and Richter, also supported in Maturana, Vilella Marcos Pereira and Freire. In the research, I face the necessity of generating spaces and times of self-production, involving practices of day-by-day micro-aesthetics. In my research results, I also acknowlede the need of exercising the authorship of educators. The study shows the contribution of day-by-day micro-aesthetics experience in training teachers in formal and informal spaces. In formal spaces, the experience day-by-day micro-aesthetics handles with the connection between popular education and critical response in their school life. In non-formal spaces, it is fundamental the conncection between the experiences of local culture and the work out of social networks. It is possible to see that the day-by-day micro-aesthetics provides the work with the artistry of the educators through freedom and authorship.